P80Cannabinoid receptor CB2 prevents development of heart failure in a murine model of pressure overload. (15th July 2014) - Duerr, GD; Heinemann, JC; Kley, J; Roell, W; Ottersbach, A; Zimmer, A; Lutz, B; Welz, A; Dewald, O
Abstract: Purpose: Cardiac adaptation to pressure overload is associated with inflammatory reaction, which untreated leads to myocardial fibrosis and heart failure. We have recently demonstrated that endogenous cannabinoids and the cannabinoid receptor 2 (CB2) are activated and associated with persistent inflammation in hypertrophic myocardium of patients with aortic valve stenosis. Therefore, we investigated the role of the CB2 in a mouse model of pressure overload. Methods: Transverse aortic constriction was performed in CB2-/–mice and their wildtype littermates (CB2+/+; n=8-12/group). Taqman ® RT-qPCR analysis was performed after 3 and 7 days. After M-mode echocardiography and Millar ® pressure-volume left ventricular catheter at days 7 and 21, hearts were harvested and subjected to immunohistochemical analysis. Results: Heart weight/tibia length-ratio and cardiomyocyte diameter as hypertrophy parameters were comparable in CB2-/–mice and their littermates after 7 and 21 days. Collagen area measurements using picrosirius red planimetry revealed a significantly increased collagen deposition in CB2+/+ mice after 7 and 21 days than in sham mice. CB2-/–mice presented with more collagen deposition than in littermates at the same time points due to intramural confluent infarcted areas. We found also significantly more α-smac positive, collagen producing myofibroblasts in the CB2-/–mice after 7 days. Echocardiography showed significant worse left ventricular function in CB2-/–mice compared to their littermates after 21 days. Analysis of inflammatory response after 3 days revealed significantly induced CCL2 mRNA-expression in CB2+/+-mice compared to sham, being also significantly higher than in the CB2-/–mice. The resolution of inflammatory response was significantly delayed in CB2-/–mice as shown by IL-10 mRNA-expression. The cellular analysis after 7 days revealed significantly higher macrophage density in both genotypes when compared to shams, whereas CB2-/–mice had significantly more macrophage accumulation than their littermates. Macrophage maturation factor osteopontin-1 was only transiently, but significantly increased in CB2+/+-mice after 7 days in contrast to the continuous increase of it in CB2-/–mice until 21 days. Conclusions: Our study suggests a cardioprotective mechanism of CB2 receptor being associated with modulation of inflammatory response and myocardial remodeling during cardiac adaptation to pressure overload in a murine model of transverse aortic constriction.